Optical Energy Transfer Mechanisms: From Naphthalene to Biacetyl in Liquids and from Pyrazine to Biacetyl - Fuat Bayrakceken; Korkut Yegin; Erdal Korkmaz; Yakup Bakis; Bayram Unal (International Journal of Photoenergy)
Optical energy transfer from naphthalene to biacetyl in liquids at room temperature is studied. Electronically excited naphthalene with 200–260 nm ultraviolet (UV) light emits photons in its emission band and the emitted photons are absorbed by biacetyl, which, in turn, excites biacetyl phosphorescence. The resulting phosphorescence is very stable with emission peak at 545 nm for different excitation wavelengths from 200 to 260 nm. Similar optical energy transfer is also observed from pyrazine to biacetyl. The sensitization of biacetyl by several aromatic donors has been investigated in detail. An aromatic donor, pyrazine, is raised to its first excited singlet state by absorption of ultraviolet radiation. Excitation wavelengths were selected in the first - band of pyrazine. Intersystem crossing in pyrazine is sufficiently fast to give a triplet yield of almost unity as determined by the biacetyl method. The optical excess energy in the biacetyl will be released as light, which is sensitized fluorescence. Biacetyl is the simplest molecule among a wide range of -dicarbonyl compounds, which is important for photophysics and photochemistry applications.